DAUN SIRSAK DAPAT MENGURANGI NYERI PUNGGUNG BAWAH PADA IBU HAMIL - Serilaila, Serilaila (JURNAL MEDIA KESEHATAN, 2013)
The arm of this research is to know the effect of giving soursop’s leaf to decrease low back pain in pregnant mother in BPM Bengkulu. This research using experimental quition method toward third semester of pregnant mother who comes to BPM, as a sample were 32 mother consist ot 16 respondens which given 5 leaves and 16 respondent give 7 leaves which was crumpled and the water stroked in the pain spot. Then all of respondent observed with pain scale before and after three time interventions observation result is analysed by univariat and bivariat with t- test. The result of the research showing the pain score before intervention is 5.22, after first intervention is 3.12, and 2.06 for second intervention and on third intervention is 0.72. the result of bivariat on 5 and 7 soursop’s leaves is p : 0,000 < 0,05 which mean’s there’s on affect in giving soursop’s leaf to decrease low back pain to third semester pregnant mother in BPM Bengkulu, meanwhile the difference of effektivity 5 and 7 sousop’s leaves is p : 0,046 < 0,05 with mean difference is 0.75. shows there isn’t difference effectivity of total leaves to decrease low back pain in third semester pregnant mother in BPM Bengkulu City.